Model of the Teacher-Philologist under the Conditions of Educational Space: Facilitative Way of Cooperation - Svitlana Piroshenko (Pedagogical Discourse, 2012)
The complex and multielement model of the teacher-philologist, which covers the range of theoretical, practical and creative competencies is viewed in the article. Emphasis is focused on dialogical integrity and facilitative way of cooperation subject-subject interaction during the educational process, person-oriented society and particular culture